Pangenome of white lupin provides insights into the diversity of the species. Issue 12 (17th September 2021) - Hufnagel, Bárbara; Soriano, Alexandre; Taylor, Jemma; Divol, Fanchon; Kroc, Magdalena; Sanders, Heather; Yeheyis, Likawent; Nelson, Matthew; Péret, Benjamin
Summary: White lupin is an old crop with renewed interest due to its seed high protein content and high nutritional value. Despite a long domestication history in the Mediterranean basin, modern breeding efforts have been fairly scarce. Recent sequencing of its genome has provided tools for further description of genetic resources but detailed characterization of genomic diversity is still missing. Here, we report the genome sequencing of 39 accessions that were used to establish a white lupin pangenome. We defined 32 068 core genes that are present in all individuals and 14 822 that are absent in some and may represent a gene pool for breeding for improved productivity, grain quality, and stress adaptation. We used this new pangenome resource to identify candidate genes for alkaloid synthesis, a key grain quality trait. The white lupin pangenome provides a novel genetic resource to better understand how domestication has shaped the genomic variability within this crop. Thus, this pangenome resource is an important step towards the effective and efficient genetic improvement of white lupin to help meet the rapidly growing demand for plant protein sources for human and animal consumption.